Karakteristik dan Kualitas Silase Rumput Raja Menggunakan Berbagai Sumber dan Tingkat Penambahan Karbohidrat Fermentable - Nur Hidayat (Agricultural Faculty, 2014)
(Characteristics and quality of king grass silages treated with various sources and level of carbohydrate fermentable)ABSTRACT . An experiment was carried out from April 1st up to August 18 th 2013. The purpose of this study was to evaluate the effect of source and level fermentable carbohydrate as an additive on the characteristic of ensilage and the contents of crude protein and crude fibre of king grass silage. The methods of this study was experimental, by using Completely Randomized Design. There were 9 treatments, each of which consisted of three replications. The treatments were : A = 1 % of mollases; B = 2 % of mollases; C = 3 % mollases; D = 5 % of rice bran E = 10 % of rice bran; F = 15 % of rice bran; G = 5 % of of cassava cake; H = 10 % of of cassava cake; I = 15 % of cassava cake. Note: all percentages were on the basis of king grass fresh weight. The observed variable were physical characteristics (color, aroma, texture, fungi), pH, temperature, and nutrient contents (crude protein and crude fibre). The result of this study showed that the color change of the silage was as follow: at the 14th and 28th day. The treatment had highly significant effect (P 0.01) on the color, texture, and fungi of the silage and the content of crude protein, and had no significant effect (P0,05) on the aroma (smell), temperature, pH and crude fibre. The contrast orthogonal test to the color, aroma, infestation of fungy, crude protein, the treatment of ABC was different relative to those of DEFGHI treatments. This study could be conclude that by wilting of king grass (water content of 60 %), the 13 of 3 % of mollases snd 5-15 % usage of rice bran an additive the results are better compared to the usage with additive of cassava cake, viewed from silages physical quality as well as its nutrient contents.